Web-Based Online Store Design at the STEBI Bina Essa Sharia Cooperative - Aisah Nur Endah Sari (JURNAL COMPUTECH & BISNIS, 2025)
The STEBI Bina Essa Sharia Cooperative offers a range of everyday necessities for its members and the general public, including products from small and medium-sized enterprises and those manufactured by its members.  Nonetheless, other obstacles persist in its operations, including inefficient record-keeping procedures, potential data inaccuracies, misplaced documents, and manual promotional and sales efforts.  Moreover, the personal selling mechanism complicates matters for consumers at a distance, as they must visit the cooperative in person and pay in cash.  This research aims to build and develop a web-based online store for the STEBI Bina Essa Sharia Cooperative.  The author utilizes the System Development Life Cycle (SDLC) technique in this study.  The findings suggest that sales may be executed online.  Suggestions for enhancing the online shop design for the STEBI Bina Essa Sharia Cooperative include using larger datasets, specifically through the implementation of a Cloud VPS.